The Thoughts of Mohammad Sjafei and Active-Creative Education - Vevi Sunarti; Listia Anita Wati; Zaiful Netra; Reza Gusmanti; Rembulan Catra Banyu Biru (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
This research aims to describe Mohammad Sjafei's educational thinking and the active-creative education system. This research is included in the literature review category and uses descriptive-interpretative methods. The author conducted a literature study to collect sources, then utilized relevant sources for the interpretation process, followed by presenting the results of the interpretation in well-structured sentences. The findings of this research describe Mohammad Sjafei as a national education figure who opened a non-formal school as an alternative school during the Dutch colonial era. He formulated his own educational curriculum which contains active-creative educational concepts. This active-creative education system provides the nation's children with the opportunity to explore their potential and develop their interests and talents to support their future careers. The aim of this education system is to form students who are independent and experts in their respective fields. This education system is able to overcome the problems of poverty and unemployment, opening up business opportunities and independence in the economic sector.